2022
DOI: 10.3390/jcm11102716
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Insight into the Role of Exosomes in Proliferative Vitreoretinopathy Development

Abstract: Purpose: To characterize vitreous humor (VH) exosomes and to explore their role in the development of proliferative vitreoretinopathy (PVR) using mass spectrometry-based proteome profiling. Methods: Exosomes were isolated from undiluted VH from patients with retinal detachment (RD) with various stages of PVR (n = 9), macular hole (MH; n = 5), or epiretinal membrane (ERM; n = 5) using differential ultracentrifugation. The exosomal size, morphology, and exosome markers were analyzed using a nanoparticle tracking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…This observation suggests a potentially biologically active status of cells in terms of sEV secretion during mid-stage maturation (28-39 days in culture), which aligns with peak therapeutic efficacy in hESC-RPE cell transplantation therapy, as opposed to earlier or later stages (Davis et al, 2017). X Notably, our previous research demonstrated higher EV particle numbers in vitreous samples from proliferative vitreoretinopathy (PVR) patients compared to non-PVR patients, supporting numbers of EV secretion is regulated either in physiologic or pathologic conditions (Nair et al,2022). 40 Despite differences in particle numbers, other characterizations of EVs, including size, morphology, and comprehensive EV profiles of the three groups of hESC-RPE-sEV, were comparable.…”
Section: Discussionmentioning
confidence: 90%
“…This observation suggests a potentially biologically active status of cells in terms of sEV secretion during mid-stage maturation (28-39 days in culture), which aligns with peak therapeutic efficacy in hESC-RPE cell transplantation therapy, as opposed to earlier or later stages (Davis et al, 2017). X Notably, our previous research demonstrated higher EV particle numbers in vitreous samples from proliferative vitreoretinopathy (PVR) patients compared to non-PVR patients, supporting numbers of EV secretion is regulated either in physiologic or pathologic conditions (Nair et al,2022). 40 Despite differences in particle numbers, other characterizations of EVs, including size, morphology, and comprehensive EV profiles of the three groups of hESC-RPE-sEV, were comparable.…”
Section: Discussionmentioning
confidence: 90%
“…Human embryonic stem cells (WA09; WiCell Research Institute, Madison, WI, USA) were spontaneously differentiated into RPE cells as previously described. 24 Briefly, colonies of hESCs were manually passaged and seeded onto tissue culture plates coated with Matrigel hESC-Qualified Matrix (#354277; Corning, Corning, NY, USA), and they received biweekly medium exchanges of XVIVO-10 culture medium (#(BE) BP04-743Q; Lonza, Walkersville, MD, USA) for approximately 3 months. Pigmented regions were then manually isolated, expanded for two passages, and cryopreserved at 2 to 5 days postseed as a cellular suspension using CryoStor10 cryopreservation medium (#210102; BioLife Solutions, Bothell, WA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…EV separation using dUC was completed as previously shown. 10 , 24 Varying input volumes of CCM (5 mL, 15 mL, 20 mL, and 30 mL) were centrifuged at 25,000 × rpm (64,000 × g ) for 60 minutes at 4°C in a Beckman Coulter Optima LE-80K (Brea, CA, USA) ultracentrifuge with rotor SW55 Ti. Then the supernatant was subjected to ultracentrifugation at 41,000 × rpm (173,000 × g ) for 120 minutes at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…The retinas from 4–6-week-old wild-type C57BL/6J mice were extracted and digested using the Papain Dissociation System (Worthington Biochemical Corporation, Lakewood, NJ, USA) according to the manufacturer’s protocol. Exosomes were recovered using differential ultracentrifugation as previously described [ 26 ]. In brief, the supernatant received from the digestion process was mixed with cold HBSS and centrifuged at 25,000× RPM for 60 min at 4 °C in a Beckman Coulter Optima L80-XP ultracentrifuge with rotor SW60 Ti.…”
Section: Methodsmentioning
confidence: 99%